2002
DOI: 10.5194/angeo-20-281-2002
|View full text |Cite
|
Sign up to set email alerts
|

<i>Letter to the Editor</i> Simultaneous observations of the ionospheric footprint of flux transfer events and dispersed ion signatures

Abstract: Abstract. We perform a case study of a favourable conjunction of overpasses of the DMSP F11 and F13 spacecraft with the field of view of the Hankasalmi HF coherent scatter. At the time, pulsed ionospheric flows (PIFs) were clearly observed at a high-latitude in the radar field of view. The PIFs were associated with medium spectral width values and were identified as the fossilized signatures of pulsed dayside reconnection. Simultaneously, DMSP spectrograms from the two spacecraft showed dispersed ion signature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 29 publications
5
26
0
Order By: Relevance
“…Steady-state aspects of the high-latitude dynamo process for the actual IMF orientation (IMF B y > 0) are discussed by, for example, Taguchi et al (1993). Our aurora-convection results are in good agreement with the recent study of Provan et al (2002), showing that the high-latitude pulsed ionospheric flows are observed within the regime of mantle precipitation and can be considered as "fossilized signatures of dayside reconnection, observed as the field lines are being pulled antisunward by the magnetosheath flow. "…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Steady-state aspects of the high-latitude dynamo process for the actual IMF orientation (IMF B y > 0) are discussed by, for example, Taguchi et al (1993). Our aurora-convection results are in good agreement with the recent study of Provan et al (2002), showing that the high-latitude pulsed ionospheric flows are observed within the regime of mantle precipitation and can be considered as "fossilized signatures of dayside reconnection, observed as the field lines are being pulled antisunward by the magnetosheath flow. "…”
Section: Discussionsupporting
confidence: 81%
“…The high-latitude phase (ii) observations appear as the recently reconnected field lines are being pulled antisunward by the magnetosheath flow. The observed flow excitation in this phase is in agreement with the previous observations/interpretations reported by for example, Sandholt et al (1993) and Provan et al (2002). PMAFs are found to be tracers of electron precipitation along poleward moving flux tubes in the convection throat which are present during a ∼5-min long phase following the initial equatorward boundary intensification.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…These flow pertubations corrugate the convection reversal boundary, as predicted by Cowley et al (1991) and Lockwood (1997). The flows at Søndrestrøm are examples of pulsed ionospheric flows which are coupled to the solar wind-magnetosphere dynamo in the HBL, along old open flux tubes that were generated at an earlier stage by a transient reconnection process (Pinnock et al, 1993(Pinnock et al, , 1995Rodger and Pinnock, 1997;Neudegg et al, 1999;Provan et al, 2002). The pulsed flows equatorward of the convection reversal (directed westward) are related to newly-opened field lines, while the channel of strong eastward flows poleward of the convection reversal is situated on older open flux coupled to the solar wind-magnetosphere dynamo in the HBL.…”
Section: Observations From the Søndrestrøm Radarmentioning
confidence: 93%
“…Individual signatures include: poleward-moving auroral forms (PMAFs; Sandholt et al, 1986Sandholt et al, , 1990Sandholt et al, , 2003, pulsed ionospheric flows/flow channels (PIFs; Pinnock et al, 1993Pinnock et al, , 1995Rodger and Pinnock, 1997;Neudegg et al, 1999;Provan et al, 2002), poleward-moving radar auroral forms (PMRAFs; Wild et al, 2001), an ion energy-latitude dispersion signature in the cusp of the staircase variety ("stepped cusp"; Cowley et al, 1991;Newell et al, 1989;Escoubet et al, 1992). The reliable and unique association of these signatures to transient reconnection requires in general multi-point observations.…”
Section: Introductionmentioning
confidence: 99%